Der Emergency Arbitrator und die ZPO - Horn, Jakob (Mohr Siebeck, 2019)
The so-called emergency arbitrator is gaining importance in international arbitration. For the first time, Jakob Horn brings it fully into line with German arbitration procedure, argues that emergency awards are enforceable under the New York Convention.
PublicationDate: 20190301
Keywords: Einstweiliger Rechtsschutz -- Schiedsverfahren -- Aufklärungszeitalter -- Geschichte Schottlands -- New York Convention on the Recognition and Enforcement of Foreign Arbitral Award -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Internationales Privatrecht -- Zivilverfahrensrecht, Insolvenzrecht